2010
DOI: 10.1002/lary.20818
|View full text |Cite|
|
Sign up to set email alerts
|

An epistaxis severity score for hereditary hemorrhagic telangiectasia

Abstract: Risk factors for increasing epistaxis severity in patients with HHT include frequency, duration, and intensity of episodes; invasiveness of prior therapy required to stop epistaxis; anemia; and the need for blood transfusion. From these factors, an epistaxis severity score will be presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
235
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(245 citation statements)
references
References 12 publications
2
235
0
8
Order By: Relevance
“…High proportion without medical or ENT review 33,34 . New data: Surgery and embolization [35][36][37][38][39] ., medical treatments 31,[40][41][42][43][44][45] …”
Section: New Data On Echo Grading and Predictive Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…High proportion without medical or ENT review 33,34 . New data: Surgery and embolization [35][36][37][38][39] ., medical treatments 31,[40][41][42][43][44][45] …”
Section: New Data On Echo Grading and Predictive Valuesmentioning
confidence: 99%
“…A recent study of 915 HHT-affected individuals indicated that a severity score based on presence of anaemia and need for transfusion in addition to four other independent factors (nose bleed frequency; duration; gushing or pouring quality; or the need for medical attention) was a significant predictor of invasiveness of therapy required for nosebleeds 33 . These data, together with the new evidence that nosebleed frequency correlates with iron and transfusional need (Fig 2), highlight the need to obtain good ENT-based reviews of anaemic patients, for specialist ENT treatments as outlined in Table 1.…”
mentioning
confidence: 99%
“…Within this period, ~180 eligible patients were approached by letter or in person. All recruited participants recorded nosebleed severity by the validated Epistaxis Severity Score (ESS) (16). This rates nosebleed severity on a scale of 0-10, with the minimal important difference recently identified as 0.71 (17).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Certain foods, often those containing high salicylate levels, have been reported to worsen epistaxis, as have low humidity and changes in temperature (34) . Various subjective grading systems are available (35,36) , and objective classification of the pattern of lesions has also been described (37) . Nasal telangiectasia are tortuous dilated superficial vessels (Figure 1), very sensitive to even the minor trauma of airflow, and a lack of elastin fibres means that they do not vasoconstrict to limit bleeding (38) .…”
Section: Clinical Featuresmentioning
confidence: 99%